Studi Eksperimental Kalor Biodiesel dari Minyak Goreng Limbah - Sembiring, Kiki Syahbana; Idris, Muhammad; Hasibuan, Yetti Meuthia; Harahap, Uun Novalia; Darianto, Darianto (CV. IRA PUBLISHING, 2024)
The ever-increasing global energy demand necessitates the development of environmentally friendly and sustainable alternative fuels. Biodiesel is a potential solution, mainly when produced from used cooking oil through the transesterification process. This study aims to evaluate the effect of reaction time on the calorific value of biodiesel using the linear regression method. The calorific value was chosen as the primary parameter because it reflects the energy produced by the fuel. The study analyzed experimental data correlating the transesterification reaction time with the biodiesel calorific value. The results showed that the optimal reaction time was 80 minutes, yielding the highest calorific value of 41.35 MJ/kg, exceeding the ASTM D6751 standard. However, the effect of reaction time on calorific value was not statistically significant, with a P-value of 0.67 and a regression coefficient of 0.02. The decrease in calorific value after 80 minutes is likely caused by overreaction, reducing efficiency. The findings indicate that reaction time is not the sole factor influencing biodiesel calorific value. Future research recommendations include incorporating variables such as reaction temperature and raw material molar ratio to enhance model accuracy. This study is expected to provide a foundation for developing high-quality biodiesel that meets international standards.